Pelatihan Berpikir Optimis Untuk Meningkatkan Harga Diri Pada Remaja di Panti Asuhan - Eka Marwati (Universitas Mathla'ul Anwar Banten, 2015)
This research aims to test empirically optimistics thinking training to improve adolescent self-esteem in the orphanage. The hypothesis is optimistics thinking training can improve adolescent self-esteem in the orphanage. The development of thinking about identity and uniqueness is a problem in the life of a teenager, one of which is associated with adolescent self-esteem. The problem that appears to be further improved, when the rate of low adolescent self-esteemas sociated with school or family migration process which is difficult and events that make teenagers depressed. Survey shows 46% of teenagers in the orphanage led to the characteristics of low self-esteem. They consider them selves do not have the establishment, be asource of problems forthe environment, estranged from the family, and to give up easily and have problems to express negative emotions. This research method uses experiment with pretest-postest control group design. Based on the results of Wilcoxon testing for pretest and posttest of experiment group gained score Z = -2,807 significance = 0,0025; p < 0,01. The conclusion of the research shows that optimistics thinking training is very efective to increase adolescent self-esteem in the orphanage.